2013
DOI: 10.1159/000356230
|View full text |Cite
|
Sign up to set email alerts
|

Use of Placebos and Nonspecific and Complementary Treatments by German Physicians - Rationale and Development of a Questionnaire for a Nationwide Survey

Abstract: Background: We are performing a nationwide survey in a random sample of German general practitioners (GPs), orthopedists, and internists on the use of placebos and nonspecific as well as complementary treatments and their association with basic professional attitudes. In this article we explain the theoretical considerations behind the study approach and the development of the questionnaire. Methods: Based on a systematic review of published surveys, own surveys on the topic, and on theoretical considerations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
12
1
1
Order By: Relevance
“…First, as other researchers have noted, it is conceptually misleading to define any substance as inert, as all substances can be treated in physico-chemical terms if one chooses to do so (Grünbaum, 1986; Howick, 2017); for example, even the classic sugar pill is not inert to a diabetic. In this sense, the distinction between ‘pure’ and ‘impure’ placebos is not just, as our findings suggest, confusing (Linde et al, 2013) but untenable.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…First, as other researchers have noted, it is conceptually misleading to define any substance as inert, as all substances can be treated in physico-chemical terms if one chooses to do so (Grünbaum, 1986; Howick, 2017); for example, even the classic sugar pill is not inert to a diabetic. In this sense, the distinction between ‘pure’ and ‘impure’ placebos is not just, as our findings suggest, confusing (Linde et al, 2013) but untenable.…”
Section: Resultsmentioning
confidence: 59%
“…Healthcare professionals and patients predominantly defined placebos as material substances (Babel, 2013; Bishop et al, 2014b; Fässler et al, 2009, 2011; Fent et al, 2011; Ferentzi et al, 2010; Hróbjartsson and Norup, 2003; Hull et al, 2013; Kermen et al, 2010; Kisaalita and Robinson, 2012; Linde et al, 2013; Nitzan and Lichtenberg, 2004; Tandjung et al, 2014). Healthcare professionals indicatively defined a placebo as a ‘pharmacological intervention, for example vitamin tablets, thus reflecting the narrow meaning of the term’ (Hróbjartsson and Norup, 2003: 162) or as ‘an inert substance that when taken by a person can have an effect on that person–either good or bad’ (Bishop et al, 2014b: 359).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies reported that placebos are indeed used by clinicians across different countries (Fassler, Meissner, Schneider, & Linde, 2010; Kermen, Hickner, Brody, & Hasham, 2010; Louhiala, 2012; Meissner, Hofner, Fassler, & Linde, 2012; Nizan, Barash, Valinsky, Lichter, & Manulis, 1997; Tilburt, Emanuel, Kaptchuk, Curlin, & Miller, 2008) including United States (Kermen et al, 2010; Sherman & Hickner, 2008; Tilburt et al, 2008), Canada (Harris & Raz, 2012; Raz et al, 2011), Germany (Linde et al., 2013; Meissner, 2005), Switzerland (Fassler, Gnadinger, Rosemann, & Biller-Andorno, 2009), Denmark (Hrobjartsson & Norup, 2003), United Kingdom (Howick et al, 2013), Israel (Nitzan & Lichtenberg, 2004), India (Shah, Panchal, Vyas, & Patel, 2009), Saudi Arabia (Hassan, Fauzi, & Hasan, 2011), and New Zealand (Holt & Gilbey, 2009). A systematic review of 22 studies from 12 different countries reported that between 17% and 80% of interviewed clinicians administered sugar pills or saline injections during their careers (Fassler et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Intentional use of placebos has been recently documented in survey studies spanning different countries including USA [76; 80; 51], Canada [69; 44], Germany [59; 57], Switzerland [30], Denmark [48], UK [47], Israel [63], India [75], Saudi Arabia [45], and New Zealand [46] (see also Table 1). A systematic review of 22 studies from 12 different countries reported that between 17 and 80% of clinicians interviewed have administered such placebo treatments as sugar pills or saline injections during their careers [32].…”
Section: Introductionmentioning
confidence: 99%